A Broadband MIMO Antenna for Access Network - Teguh Prakoso; N Shazwani M. Noor; E. H. Hadyan; M. A. Riyadi; Razali Ngah (IAES Indonesia Section, 2015)
This paper presents a compact and broadband MIMO antenna intended for wireless access network at 1.7 – 6.0 GHz. Impedance degradation introduced by half-cut technique is solved by inserting microstrip-line transformer.